2005
DOI: 10.1080/10915810500259556
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Tripeptides (L-Valyl-L-prolyl-L-proline and L-lsoleucyl-L-prolyl-L-proline): III. Single- and/or Repeated-Dose Toxicity of Tripeptides-Containing Lactobacillus helveticus-Fermented Milk Powder and Casein Hydrolysate in Rats

Abstract: The objective of these studies was to assess the toxicological potential of orally administered tripeptides in rats. The studies employed powdered L-valyl-L-prolyl-L-proline (VPP)- and L-isoleucyl-L-prolyl-L-proline (IPP)-containing test articles, including (1) powdered Lactobacillus helveticus-fermented milk (FM), (2) pasteurized casein hydrolysate (CH) generated by Aspergillus oryzae protease, and (3) synthesized VPP. All test articles were administered by oral gavage to male and female Sprague-Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…Maeno, Nakamura, Mennear, and Bernard (2005) reported that casein hydrolysates and Val-ProPro sourced from powdered fermented milk exerted no specific target organ toxicity. Similarly, there appears to be no evidence to support establishment of either the Lowest Observed Effect Level (LOEL) or Maximally Tolerated Dose (MTD); both being greater than 2 g kg À1 day À1 for up to 28 consecutive days in rats.…”
Section: Safety Aspects Of Casein Hydrolysatesmentioning
confidence: 98%
“…Maeno, Nakamura, Mennear, and Bernard (2005) reported that casein hydrolysates and Val-ProPro sourced from powdered fermented milk exerted no specific target organ toxicity. Similarly, there appears to be no evidence to support establishment of either the Lowest Observed Effect Level (LOEL) or Maximally Tolerated Dose (MTD); both being greater than 2 g kg À1 day À1 for up to 28 consecutive days in rats.…”
Section: Safety Aspects Of Casein Hydrolysatesmentioning
confidence: 98%
“…However, the antihypertensive effect of fermented milk is still debatable. In three recent human studies -two of them including multicentre, double-blind, parallel, placebo-controlled trials -no blood pressure-lowering effect 56 R. Sieber et al…”
Section: Quantification Of Aceinhibiting Peptides During Cheese Ripeningmentioning
confidence: 99%
“…A recent study was conducted to evaluate the safety of two tripeptides, L-valyl-L-prolyl-L-proline (VPP) and L-isoleucyl-L-prolyl-L-proline (IPP) extracted from milk fermented by L. helveticus. The authors found that there was no evidence of either systemic or local toxicity in rats in a 28 days trial (Maeno, Nakamura, Mennear, & Bernard, 2005).…”
Section: Discussionmentioning
confidence: 97%